THE EFFECT OF WORK INTERFERE FAMILY AND FAMILY INTERFERE WORK ON COMMITMENTS THROUGH SATISFACTION AND MOTIVATION - karya, denis fidita; rasyid, reizano amri; candraningrat, candraningrat (Universitas Dr. Soetomo, 2021)
This research was conducted to determine how the influence of work-family conflict (WFC), which consists of work interfere conflict (WIF) and family interfere conflict (FIW) factors on organizational commitment through the mediation of job satisfaction and work motivation on women entrepreneurs in Surabaya. The data collection technique in this study is a survey method using a questionnaire instrument filled out by respondents. The population in this study were all female entrepreneurs in the city of Surabaya. The number of samples in this study was 310 people. In this study, the data analysis method used was Partial Least Square (PLS) with SmartPLS 2.0 software. The results of the research are expected that WIF and FIW negatively affect entrepreneurial commitment through mediating job satisfaction and work motivation.